PENGEMBANGAN KOMPETENSI APARATUR DALAM MENINGKATKAN KINERJA PEGAWAI DI DINAS KELAUTAN DAN PERIKANAN PROVINSI KALIMANTAN TIMUR - Agung Sugiarto (Jurnal Administrative Reform, 2019)
The purpose of this study is to describle and analize the Competency Development Resource Apparatus in Improving Employee Performance in the Marine and Fisheries Agency of East Kalimantan. This type of research is descriptive with qualitative approach. Drawing conclutions based on the data were processed using data analysis interactive model. Based on the results of this study concluded that the competence development of the personel in the Department of Marine and Fisheries, East Kalimantan Province which is implemented through education and technical training, education and leadership training, career development and adds yet optimal work experience  carried out but benefits have been felt able to improve employee performance. Keyword: apparatur, performance, resource, competence